2016
DOI: 10.1186/s12966-016-0430-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity throughout adolescence and body composition at 18 years: 1993 Pelotas (Brazil) birth cohort study

Abstract: BackgroundAdolescence is a period of accelerated development and increases in body composition. Physical activity (PA) practice has been associated with the development of major components of body composition (bone, muscle and fat). However, the longitudinal effects of PA of different intensities during adolescence are still not well understood. Thus, the main goal this study has investigate the association between practice of moderate- and vigorous-intensity physical activity throughout adolescence and body c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 70 publications
2
25
1
4
Order By: Relevance
“…this hypothesis is supported by the results of a prior study in which adolescents who completed scheduled PA for one year presented with BMI stability, lean mass increase, and fat mass reduction in the triceps region [7]. therefore, the findings of the present study, and of other studies mentioned above [2,7,10,24] reinforce the hypothesis that BMI measurements must be carefully interpreted especially among physically active adolescents. due to the risk of misclassifying male adolescents who meet PA requirements as being overweight, the use of a more accurate assessment of body composition is strongly recommended.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…this hypothesis is supported by the results of a prior study in which adolescents who completed scheduled PA for one year presented with BMI stability, lean mass increase, and fat mass reduction in the triceps region [7]. therefore, the findings of the present study, and of other studies mentioned above [2,7,10,24] reinforce the hypothesis that BMI measurements must be carefully interpreted especially among physically active adolescents. due to the risk of misclassifying male adolescents who meet PA requirements as being overweight, the use of a more accurate assessment of body composition is strongly recommended.…”
Section: Discussionsupporting
confidence: 90%
“…this finding is consistent with previous systematic reviews which found that, regardless of the method used to estimate adolescents' body fat, BMI measurements' sensitivity to detect fat mass is low [4] and that PA is inversely related to fat mass but not to BMI [12]. Additionally, researchers controlling for physical growth and biological maturation found that PA explains 21% of the increase in lean muscle mass [10] and that physically active adolescents who maintain such condition present with higher amounts of lean mass in comparison with their insufficiently active peers [24]. Conversely, in a population study performed with adults with the same BMI, it was found that those that were physically active presented a greater percentage of body fat [2].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, The Healthy Lifestyle in Europe by Nutrition in Adolescence study failed to find an association between physical activity and fat-free mass in Spanish adolescents aged 12.5-17.5 years (33). Moreover, longitudinal studies observed that habitual physical activity had a significant independent influence on the growth of lean body mass during adolescence (34,35). Taken together, all of these studies have not considered dietary factors as potential confounding variables, which may be one of the reasons leading to the inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that even a small difference in lean mass may have a substantial effect on increase in fat mass, since muscles are particularly important for oxidisation of fat . Another study found that those with higher lean mass could have higher resting metabolism through the effect of increased muscle mass . The effect of regular physical activity on lean mass is, therefore, important when it comes to preventing overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%